Effects of aqua drugs and chemicals on the farmed shrimp (Penaeus monodon) in southern coastal region of Bangladesh (Asian Journal of Medical and Biological Research, 2020)
The study was conducted to observe the effects of aqua drugs and chemicals on the health of farmed shrimp (Penaeusmonodon) in southern coastal region of Bangladesh. Samples were collected from shrimp farms and ghers in three upazilas of Cox’s Bazar district, namely Cox’s Bazar Sadar, Teknaf and Maheshkhaliupazila during March 2018 to October 2018. Data were collected through personal contact, questionnaire interview and discussion with key informants. During the study period water temperature were ranged between 26°C to 32°C in summer and 23°C in rainy season. The highest pH was 8.0 ± 0.20 recorded from Beximco Shrimp Farm of Cox’s Bazar Sadar in summer and the lowest was 7.0 ± 0.23 from the Aquaculture Farm Limited of Cox’s Bazar Sadar. Farmers in the study areas used Geotox to remove gas, TSP to proliferate algae and Zymetin to inhibit growth of pathogens and to promote shrimp growth. The highest recovery was recorded 90-96% by use of Bleaching powder in Aquaculture Farm limited of Cox’s Bazar Sadar area. On the other hand, the lowest recovery was recorded 60-65% by use of Zeolite plus in Beximco shrimp farm of Cox’s Bazar Sadarupazila. The average recovery was recorded from Beximco shrimp farm of Cox’s Bazar Sadarupazila. By use of EcodoxinZoothamniumwas 80-85% recovery. Farmers used more aqua-drugs in rainy season than summer. By use of Oxyflow instant oxygen supply was recorded 75-80% recovery. The highest recovery was recorded 90-95% by use of Lime in Unique Aquaculture of Teknaf. On the other hand, the lowest recovery was recorded 60-65% by use of Renamox in MKA shrimp farm of Teknafupazila. The average recovery was recorded Unique Aquaculture of Teknafupazila. From field and laboratory observations it was revealed that the study area had potentiality for shrimp culture, although necessary measures need to be taken specially during rainy season.Asian J. Med. Biol. Res. September 2020, 6(3): 491-498